Resíduos medievais da simbologia cristã no romance A Rainha do Ignoto de Emília Freitas - Morais, Cícero Bôscoly Mangueira de (2023)
The research object of study is the novel A Rainha do Ignoto, by Emília Freitas. The general objective is to investigate how Christian symbolism is configured as a medieval residue in the work in question, that is, to analyze these remnants in the 19th century, the time in which the book was written, identifying the sacred and the profane both in the characters' routine who live in the village of Passagem das Pedras, as well as the way of life of Funesta and her paladins, who inhabit Ilha do Nevoeiro, and investigate the medieval dualism, present in the novel, from the perspective of the Theory of Residuality. The theoretical foundations that support this work will have as reference the authors of the Theory of Residuality and their concepts of residue, mentality and imaginary of PONTES (2017), in addition to two medieval categories: “the sacred and the profane”, based on the studies of DUBY and PERROT (1990); LE GOFF (1991); FRANCO JR. (1994), among other medievalists who will be necessary throughout the research. TODOROV (2017) studies also contribute to analyzing the presence of Fantasy Literature in the work. To analyze the condition of women in the context in which the work is inserted, both from the perspective of the characters and from Emília Freitas' way of thinking, we also appropriate concepts from feminist criticism, represented by the ideas of DUARTE (1990). The methodology will be based on bibliographical research, based on the appropriation of concepts from the theory of Residuality concepts, as well as the study of the author and the work.